Medulloblastoma biology in the post-genomic era. (December 2012) - Archer, Tenley C; Pomeroy, Scott L
Medulloblastomas, the most common malignant pediatric brain tumors, are comprised of four molecularly distinct subtypes. However, treatment has yet to exploit these molecular vulnerabilities. Three recent studies sequenced a total of 310 primary tumors and identified that two of the four medulloblastoma subtypes are concomitantly associated with subtype-specific mutations as previously characterized. In contrast, the overwhelming majority of mutations occurred only once in the entire cohort and just 12 genes were recurrently mutated with statistical significance. Perturbations in epigenetic regulation are emerging as a unifying theme in cancer and similarly recurring mutations in epigenetic mechanisms were distributed across all subtypes in medulloblastoma. Designing targeted therapies to such a molecularly diverse disease in the post-genomic era presents new challenges. This will require novel methods to link these nonrecurrent mutations into pathways, and preclinical models that faithfully recapitulate patient driver events. Presently, medulloblastoma reinforces epigenetic mechanisms as a tantalizing therapeutic target in cancers.